2014
DOI: 10.18524/1815-7459.2005.1.112261
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Air Pollution Field Structure in the Industrial City’s Atmosphere: Stochasticity and Effects of Chaos

Abstract: SENSING AIR POLLUTION FIELD STRUCTURE IN THE INDUSTRIAL CITY'S ATMOSPHERE: STOCHASTICITY AND EFFECTS OF CHAOSA. V. Glushkov, Yu. Ya. Bunyakova, V. N. Khokhlov, G. P. Prepelitsa and I. A. TsenenkoA new scheme for sensing temporal and spatial structure of the air pollution fields in the industrial city's atmosphere is considered and applied to an analysis of the Odessa atmosphere aerosol component data. Effects of stochasticity and chaotic features in the dusty air pollution field structure are discovered on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…One of the actual problems of modern atmosphere and environmental physics is carrying out new, effective schemes for sensing air pollution field structure in atmosphere in general and atmosphere of industrial cities in particular (c. f. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). A great number of different experimental methods are used in studying the atmosphere pollution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the actual problems of modern atmosphere and environmental physics is carrying out new, effective schemes for sensing air pollution field structure in atmosphere in general and atmosphere of industrial cities in particular (c. f. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). A great number of different experimental methods are used in studying the atmosphere pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In last years it has been shown that the aerosol particles are created in many natural processes (coagulation of smoke particles, clusters in the clouds, etc.) and possessed by the fractal structure (c. f. [2][3][4][5][6][7][8][9][10][11][12][13][14][15]). Papers [15][16][17][18] have been devoted to development of new, effective theoretically optimal technological schemes for sensing temporal and spatial structure of the air pollution fields in the industrial city's atmosphere and creation of the corresponding laser emission analysis methodises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…У вивченні антропогенного впливу на екологічний стан атмосфери промислового міста мето-ди теорії хаосу дозволяють, наприклад, на основі до-слідження часових рядів концентрацій забруднюючих атмосферу промислового міста речовин давати цілком адекватний аналіз і навіть короткостроковий прогноз подальшої часової еволюції концентрацій забруднюю-чих речовин [3][4][5][6][7][8][9][10][11][12][13][14]. Такий підхід з успіхом використову-вався при аналізі флуктуацій метеорологічних та гідро-логічних характеристик [15][16][17].…”
unclassified
“…Такий підхід з успіхом використову-вався при аналізі флуктуацій метеорологічних та гідро-логічних характеристик [15][16][17]. У роботах [3][4][5][6] методи нелінійного прогнозу і теорії хаосу з успіхом застосову-валися до аналізу часових рядів концентрацій пилу, діоксиду сірки на двох стаціонарних постах м. Одеси, а також в ряді міст Гданського регіону. Було показано, що навіть спрощена методика побудови прогностичної мо-делі дає цілком задовільні результати прогнозу.…”
unclassified